Проблеми дослідження міської логістики у містах України - Ольхова, Марія; Рославцев, Дмитро (ТзОВ «Галицька видавнича спілка», 2021)
This research is dedicated to the issue of data collection for solving city logistics problems in the Ukrainian cities namely statistical data, GPS data, Automated Vehicle Monitoring.
Challenges of research of city logistics in the Ukrainian cities
Keywords: 656.073